2020
DOI: 10.3329/cardio.v12i2.47986
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraoperative Loading Dose of Amiodarone for Prophylaxis Against Atrial Fibrillation in Patients with Rheumatic Valvular Heart Disease Undergoing Valve Replacement Surgery

Abstract: Background: Atrial Fibrillation (AF) is the most common arrhythmia occurring after cardiac surgery and its peak incidence is between second or third postoperative day. It occurs in 40% to 50% of patients after valve surgery alone or combined valve and CABG surgery respectively. Among all the anti-arrhythmic drugs evaluated for AF, amiodarone has shown the most promising results with successful conversion and maintenance of normal sinus rhythm achieved in 50%–70% of patients. Methods: Sixty diabetic patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In the amiodarone group, ventricular tachycardia manifested in 6.7% of patients and atrial fibrillation was identified in 26.7% of patients. 13 Sasa et al explained that in patients who received amiodarone in the post-operative period the incidence of AF was reduced. 16 According to Atreya et al and Thanavero et al, patients receiving peri-operative amiodarone had reduced risk of atrial arrhythmias and AF than those without prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In the amiodarone group, ventricular tachycardia manifested in 6.7% of patients and atrial fibrillation was identified in 26.7% of patients. 13 Sasa et al explained that in patients who received amiodarone in the post-operative period the incidence of AF was reduced. 16 According to Atreya et al and Thanavero et al, patients receiving peri-operative amiodarone had reduced risk of atrial arrhythmias and AF than those without prophylactic treatment.…”
Section: Discussionmentioning
confidence: 99%